Enhancing Strength Characteristics of Black Cotton Soil Through Combined Stabilisation using Coal Tailings and Calcium Lignosulfonate - Motepalli, Venu; Viswanathan, Sampathkumar (Archives of Mining Sciences, 2026)
The present study investigates the potency of stabilising a problematic Black Cotton (BC) soil using a combination of coal tailings and calcium lignosulphonate to address the subgrade problems of a part of the Narsapur-Aswaraopeta major highway. The BC soil creates problems in the construction and maintenance of road pavements in this region. An exhaustive experimental programme was performed on treated BC soil to evaluate the impact of distinct Coal Tailings of 0-20% and Calcium Lignosulfonate of 0-5% dosage. The results revealed that the optimal combination of 12% Coal Tailings and 4% Calcium Lignosulfonate yielded a rise in Maximum Dry Density, California Bearing Ratio, and Unconfined Compressive Strength of the treated soil. These improvements are attributed to the development of Calcium Silicates and Calcite, as established through X-Ray Diffraction analysis and densification of the soil matrix observed through Field Emission Scanning Electron Microscopy. The Energy-Dispersive X-Ray Spectroscopy showed the alterations in primary composition, indicating the interaction between stabilisers and the BC soil. The analysis made on the optimum CBR value with corresponding pavement thicknesses revealed that the pavement thickness with the combinedly treated BC soil was greatly decreased to 290 mm. The combined stabilisers treatment proved significantly more effective than individual stabilisation methods, offering a promising approach for improving the geotechnical characteristics of challenging BC soil for subgrade construction and other geotechnical applications.